Walking away : refusing and resisting reactionary curriculum movements - Pratt, Alexander B.; Donley, Kevin; Hatch, Sage; Tharp, Staci L.; Calderon-Berumen, Freyca (Curriculum and pedagogy series., 2024)
Walking away is both refusal and production (Tuck & Yang, 2014), a seeming paradox taken up in work on fugitivity and marronage (Diouf, 2021; Grant, Woodson, & Dumas, 2021; Harney & Moten, 2013; Hartman, 2007), survivance (Powell, 2002; Sabzalian, 2019; Vizenor, 2008), testimonios (Calderon-Berumen, 2021; Delgado Bernal, Burciaga, & Flores Carmona, 2012; Latina Feminist Group, 2001), and other forms of critical pedagogy and curriculum. In other words, walking away presumes both the rejection of a form of status quo (walking away from something) and a new direction taken (a walking toward something else). In the context of education, many teachers and researchers have reached that breaking point where/when no more curricular/pedagogic violence can be survived, and it is in that moment that those researchers and teachers actively remove themselves from those systems and assert new courses with new possibilities.This edited volume is a collection of works chronicling acts of refusal that manifest as walking away. In some cases what is walked away from is the erasure of experience in curriculum while in others it is a fundamentalist religious experience. In still other cases what is walked away from is the carceral nature of school discipline policies. In each case walking away is resistance, refusal, and re/co-producing new possibilities and agencies. What is walked toward is a new curriculum/pedagogy of resistance sometimes within and sometimes without that place.